Efeito da fotobiomodulação sobre macrófagos submetidos à ação do veneno de B. jararacussu - Campos, Gabriela Russo Soeiro (2020)
Bothrops snake venom induces serious inflammatory events, including leukocyte migration and a complex network of mediators released. Leukocyte infiltration is characterized by an initial influx of neutrophils followed by a late infiltration of mononuclear cells, which accumulates at the injection site and in the surrounding tissues. Studies carried out by our group show that the treatment with photobiomodulation (PBM) associated with serotherapy decreases the leukocyte influx, in vivo, improving an inflammatory condition, but the mechanism by which photobiomolulation acts on the inflammatory reaction associated with the venom is unknown. Thus, the objective of this study was to evaluate the mechanism of action of PBM in RAW 264.7 macrophages incubated with botropic venom. For this, the cells were incubated with B. jararacussu venom (BjsuV), and immediately irradiated with Low level Laser with the following parameters: λ 660 nm wavelength, 100 mW power (power density 0.33 W / cm2), beam area 1 cm2, with an energy density of 4 J / cm2 and a time of 40 seconds, and were incubated at 1, 3, 6 and 24 h. The effect of PBM on cell viability was analyzed. In addition, the release of pro- and anti-inflammatory cytokines (IL-1, IL-6, TNF-α and IL-10) was analyzed by immunoenzymatic assay and intracellular calcium. The results obtained from the response curve showed no decrease in cell viability at any concentration used in the period of 1 h, in the period of 6 h all concentrations used demonstrated a decrease in cell viability. PBM caused a significant increase in cell viability, compared to the untreated group. The BjsuV group induced the release of IL-6, IL-1β with a significant difference at all period of time studied, with greater release at 3 h and TNF-α at 1 and 6 h. In addition, it showed a significant decreased in the release of IL-10, within 6 and 24 h. PBM decreased levels of TNF-α, at times 1 and 6 h, of IL-6, at times 3 and 6 h, at IL-1β, decreased levels at all times studied, and increased the release of IL -10 at 6 and 24 h. The BjsuV group showed a decrease in measurement of intracellular Ca2+, when compared to the control. PBM caused a significant increase in Ca2+. These data suggest that the protective effect of PBM on macrophages must be, at least in part, by decreasing pro-inflammatory cytokines and increasing anti-inflammatory.